APPROXIMATIONS ON THE RIGHT TO EXAMINE AND CROSS-EXAMINE: THE USE OF SUGGESTIVE QUESTIONS IN THE ORAL PROCEEDINGS - García Curiel, Karen Dalina (2025)
This paper shows that judges often impose limitations on the use of leading questions in cross-examination during oral trials. In this sense, considering that conceptual and substantiation gaps have an unquestionable impact on the protection of human rights, the authors specify in this documentary research the inherent aspects of the concept and foundation of the right to examine and cross-examine to prevent the vagueness of these elements from causing this right to be unprotected.